‘Ambivalence’ at the end of life: How to understand patients’ wishes ethically - Ohnsorge, Kathrin (Nursing ethics, 2012)
Health-care professionals in end-of-life care are frequently confronted with patients who seem to be ‘ambivalent’ about treatment decisions, especially if they express a wish to die. This article investigates this phenomenon by analysing two case stories based on narrative interviews with two patients and their caregivers. First, we argue that a respectful approach to patients requires acknowledging that coexistence of opposing wishes can be part of authentic, multi-layered experiences and moral understandings at the end of life. Second, caregivers need to understand when contradictory statements point to tensions in a patient’s moral experience that require support. Third, caregivers should be careful not to negatively label or even pathologize seemingly contradictory patient statements.